Evaluating macroprudential policies - Claudia M. Buch; Edgar Vogel; Benjamin Weigert (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2018)
Macroprudential policy is a relatively new policy field. Its goal is to preserve financial stability and to prevent the build-up of systemic risk that may have adverse effects for the functioning of the financial system and for the real economy. New institutions have been tasked with the implementation of macroprudential policies, and new policy instruments have been introduced. Nonetheless, uncertainty about the state of the financial system and the effects and effectiveness of these policy instruments is high. This uncertainty entails two risks: the risk of acting too late (inaction bias) and the risk of choosing an inappropriate instrument or inadequate calibration. In this paper, we argue that both risks can be mitigated if macroprudential policy is embedded in a structured policy process. Such a policy process involves four steps: defining policy objectives for macroprudential policies, choosing intermediate objectives and appropriate indicators, linking instruments to these indicators through ex-ante evaluation studies, and analyzing the effects of these policies through ex-post evaluation studies. We argue that the infrastructure for this policy process can be further improved by providing data for policy evaluation, establishing or strengthening legal mandates for policy evaluation, establishing mechanisms for international cooperation, and building up repositories of evaluation studies.
Keywords: G01; F34; G21; 330; Macroprudential policy; financial regulation; policy evaluation